OP0100 Gout in patients with stable coronary heart disease and the impact of serum uric acid levels on adverse cardiovascular outcomes: A long-term follow-up study. (23rd January 2014) - Rothenbacher, D.; Kleiner, A.; Koenig, W.; Primatesta, P.; Breitling, L.P.; Brenner, H.
Abstract : Background: A relationship between hyperuricemia or gout and cardiovascular disease has been described in many studies. However, it is unclear whether the association between serum uric acid (SUA), inflammatory cytokines and risk of atherosclerosis is causal or an epiphenomenon. Objectives: To investigate the independent prognostic relationship of SUA and inflammatory markers with adverse cardiovascular outcomes in a patient population with stable coronary heart disease (CHD) at baseline under special consideration of gout. Methods: CHD patients aged 30-70 from two cooperating German hospitals were enrolled (January 1999 - May 2000) and followed up for 8 years. Self-reported gout diagnosis was ascertained at baseline. The relation of SUA and inflammatory markers (CRP; IL-6) with subsequent CVD (fatal or non-fatal MI or stroke) was assessed by Kaplan-Meier and Cox proportional hazards, adjusting for know confounders for CVD events. Results: 1, 056 patients were included, of whom 229 reported at baseline a diagnosis of gout. Patients with gout at baseline had a less favourable cardiometabolic profile: higher CRP, IL-6 and SUA. Overall, 151 patients out of 1, 056 (incidence 21.1 per 1000 patient-years) experienced subsequent fatal or non-fatal CVD. This incidence was positively correlated with SUA and CRP in Kaplan-Meier plots (p=0.003 and p=0.002 respectively). After adjustment for age, gender and hospital site the hazard ratio (HR) for SUA increased from 1.53 to 1.74 and 2.80 in the second, third, and top quartile, when compared to the bottom one (p for trend <0.0001). The presence of clinical diagnosis of gout did not enhance this association. The relationship between CRP and subsequent CVD was not statistically significant. Conclusions: The data suggest that, irrespective of the presence of gout, SUA (in contrast to CRP) predicts future CVD risk in patients with stable CHD with a risk increase even at levels considered normal, and therefore may contribute independently to the pathophysiology of CVD events. Disclosure of Interest: D. Rothenbacher: None Declared, A. Kleiner: None Declared, W. Koenig: None Declared, P. Primatesta Employee of: Novartis, L. Breitling: None Declared, H. Brenner: None Declared